Symbol and Theme on Robert Frost’ Poem by Using Biographical Perspective - Wiruma Titian Adi (LINGUA : Jurnal Bahasa, Sastra, dan Pengajarannya, 2020)
The objective of this research was to find out the symbol and theme that was used by Robert Frost in his literary works. It was also to elaborate on his biographical aspect of using symbols and themes in his poem. The method used to make this paper was a qualitative method. The writer also used two approaches to analyze this paper; first, the intrinsic approach consists of the symbol and theme and second, the extrinsic approach is a biographical perspective. The data were collected through library research. The results of this research indicated that the symbol on “Stopping by Woods on a Snowy Evening” was related to his nature or everyday life, while the theme on “Stopping by Woods on a Snowy Evening” was about the journey. The last, Robert Frost wrote his poem based on his experience of life when he was a teenager.